Diabetes-specific formula with standard of care improves glycemic control, body composition, and cardiometabolic risk factors in overweight and obese adults with type 2 diabetes: results from a randomized controlled trial - Tey, Siew Ling; Chee, Winnie S.S.; Deerochanawong, Chaicharn; Berde, Yatin; Lim, Lee-Ling; Boonyavarakul, Apussanee; Wakefield, Brittany; Baggs, Geraldine; Huynh, Dieu Thi Thu (Frontiers in Nutrition, 2024)
Medical nutrition therapy is important for diabetes management. This randomized controlled trial investigated the effects of a diabetes-specific formula (DSF) on glycemic control and cardiometabolic risk factors in adults with type 2 diabetes (T2D). Participants (n = 235) were randomized to either DSF with standard of care (SOC) (DSF group; n = 117) or SOC only (control group; n = 118). The DSF group consumed one or two DSF servings daily as meal replacement or partial meal replacement. The assessments were done at baseline, on day 45, and on day 90. Results showed significant reductions in glycated hemoglobin (-0.44% vs. -0.26%, P = 0.015, at day 45; -0.50% vs. -0.21%, P = 0.002, at day 90) and fasting blood glucose (-0.14 mmol/L vs. +0.32 mmol/L, P = 0.036, at day 90), as well as twofold greater weight loss (-1.30 kg vs. -0.61 kg, P < 0.001, at day 45; -1.74 kg vs. -0.76 kg, P < 0.001, at day 90) in the DSF group compared with the control group. The decrease in percent body fat and increase in percent fat-free mass at day 90 in the DSF group were almost twice that of the control group (1.44% vs. 0.79%, P = 0.047). In addition, the percent change in visceral adipose tissue at day 90 in the DSF group was several-fold lower than in the control group (-6.52% vs. -0.95%, P < 0.001). The DSF group also showed smaller waist and hip circumferences, less fat mass and visceral adipose tissue, and lower diastolic blood pressure than the control group (all overall P ≤ 0.045). DSF with SOC yielded significantly greater improvements than only SOC in glycemic control, body composition, and cardiometabolic risk factors in adults with T2D.